2018
DOI: 10.1038/s41401-018-0087-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification, structure modification, and characterization of potential small-molecule SGK3 inhibitors with novel scaffolds

Abstract: The serum and glucocorticoid-regulated kinase (SGK) family has been implicated in the regulation of many cellular processes downstream of the PI3K pathway. It plays a crucial role in PI3K-mediated tumorigenesis, making it a potential therapeutic target for cancer. SGK family consists of three isoforms (SGK1, SGK2, and SGK3), which have high sequence homology in the kinase domain and similar substrate specificity with the AKT family. In order to identify novel compounds capable of inhibiting SGK3 activity, a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…1315 Due to the high homology of their SGK catalytic domains, it has not been possible to elaborate inhibitors that display isoform specificity. 16 These compounds could have less toxicity for treating cancer resistance than inhibitors targeting all isoforms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1315 Due to the high homology of their SGK catalytic domains, it has not been possible to elaborate inhibitors that display isoform specificity. 16 These compounds could have less toxicity for treating cancer resistance than inhibitors targeting all isoforms.…”
mentioning
confidence: 99%
“…These data support the notion of targeting SGK3 as a therapeutic strategy for counteracting resistance to PI3K/Akt inhibition in cancer treatment. A number of ATP competitive inhibitors that target all SGK isoforms with similar affinity have been reported. Due to the high homology of their SGK catalytic domains, it has not been possible to elaborate inhibitors that display isoform specificity . These compounds could have less toxicity for treating cancer resistance than inhibitors targeting all isoforms.…”
mentioning
confidence: 99%
“…The IC 50 values determined in this study are comparable to reported values. 28,29 To further validate the FP assay, the selective SGK inhibitor GSK650394 was chosen as a reference compound, which revealed IC 50 values of 0.033, 0.093, and 5.0 µM for SGK1, SGK2, and SGK3, respectively ( Suppl. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[ 114 ] Thus, the inhibition of SGK3 could constitute a relevant therapeutic target in cancer treatment but, due to the high homology of the SGK ATP domain, it has not been possible to produce until now specific ATP competitive inhibitors that only targeting one isoform of the SGK family. [ 115 ] In this context, the conversion into PROTACs of SGK inhibitors seems to be a reasonable solution to obtain selective compounds that only target one SGK isoform due to the potential increasing selectivity property of PROTAC compounds.…”
Section: Serine‐threonine Kinases (Stks) Degradersmentioning
confidence: 99%